2000
DOI: 10.1038/sj.mp.4000760
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 receptor protein is elevated in nucleus accumbens of human, chronic methamphetamine users

Abstract: Animal data have long suggested that an adaptive upregulation of nucleus accumbens dopamine D1 receptor function might underlie part of the dependency on drugs of abuse. We measured by quantitative immunoblotting protein levels of dopamine D1 and, for comparison, D2 receptors in brain of chronic users of methamphetamine, cocaine, and heroin. As compared with the controls, brain dopamine D1 receptor concentrations were selectively increased (by 44%) in the nucleus accumbens of the methamphetamine users, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 46 publications
6
50
0
Order By: Relevance
“…Several recent reports have indicated that amphetamine alters dopamine receptor expression in adult humans, animals or cell cultures [Worsley et al, 2000;Tong et al, 2003]. These data provide additional support for the hypothesis that overactivity of the DRD1 system might underlie some of the features of dependence on psychostimulant drugs.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Several recent reports have indicated that amphetamine alters dopamine receptor expression in adult humans, animals or cell cultures [Worsley et al, 2000;Tong et al, 2003]. These data provide additional support for the hypothesis that overactivity of the DRD1 system might underlie some of the features of dependence on psychostimulant drugs.…”
supporting
confidence: 69%
“…These reports, taken together with the demonstration that DRD1 agonists can prevent relapse to drug-seeking behavior in rodent [Self et al, 1996] have provided an experimental platform for the selec-tion of the DRD1 as a clinical target for therapeutic intervention in human drug users. In a recent human study, protein levels of DRD1 in the brain of chronic METH users were selectively increased in the NAc [Worsley et al, 2000].…”
Section: Drd1 Upregulationmentioning
confidence: 99%
“…However, the few human studies that have assessed DA D2 receptors in METH abusers have not shown marked decreases in these parameters. For example, in [ 11 C]raclopride-PET studies, decreases in DA D2 receptor availability of only 10% in putamen and 16% in caudate were measured (Volkow et al, 2001) while a post-mortem study showed a trend of 25% decreases in D2 receptor protein levels (Worsley et al, 2000). The range of cumulative METH exposure patterns for those individuals may have contributed to the variability of those measures.…”
Section: Brain Alterationsmentioning
confidence: 99%
“…In addition, an animal's level of sucrose preference can predict its desire to self-administer cocaine (Levine et al, 2003), and sweets will reduce cocaine's reinforcing value (Comer, Lac, Wyvell, & Carroll, 1996), suggesting a relation between sweet taste and drug reward. Both obese rats and chronic drug users have low basal dopamine levels (Hamdi, Porter, & Prasad, 1992), experience periodic exaggerated dopamine release associated with either food (Fetissov et al, 2002) or drug intake (Worsley et al, 2000), and have reduced dopamine D2 receptor and increased D1 receptor expression (Fetissov et al, 2002). A number of addictive behaviors (alcoholism; cocaine, heroin, marijuana, and nicotine use; and glucose bingeing) have been associated with low expression or dysfunction of D2 receptors (Comings & Blum, 2000).…”
Section: Common Neurobiological Substrates For Obesity and Drug Addicmentioning
confidence: 99%